Maximum likelihood and economic modeling - Gauthier Lanot (IZA World of Labor, 2017)
Most of the data available to economists is observational rather than the outcome of natural or quasi experiments. This complicates analysis because it is common for observationally distinct individuals to exhibit similar responses to a given environment and for observationally identical individuals to respond differently to similar incentives. In such situations, using maximum likelihood methods to fit an economic model can provide a general approach to describing the observed data, whatever its nature. The predictions obtained from a fitted model provide crucial information about the distributional outcomes of economic policies.
Keywords: C5; J2; H3; 330; log-likelihood; economic model; parameter estimates